Fooled by Randomness: The Hidden Role of Chance in Life and in the Markets (Incerto #1) - Nassim Nicholas Taleb (New York Random House Trade Paperbacks, 2005)
Fooled by Randomness is a standalone book in Nassim Nicholas Taleb's landmark Incerto series, an investigation of opacity, luck, uncertainty, probability, human error, risk, and decision-making in a world we don't understand. The other books in the series are The Black Swan, Antifragile,and The Bed of Procrustes.
Keywords: Investments; Random variables; Chance; Business; Economics; Nonfiction; Philosophy; Psychology; Science